Purification and characterization of a lectin from the white shrimp Litopenaeus setiferus ( Crustacea decapoda) hemolymph - Alpuche, Juan; Pereyra, Ali; Agundis, Concepción; Rosas, Carlos; Pascual, Cristina; Slomianny, Marie-Christine; Vázquez, Lorena; Zenteno, Edgar (Biochimica et biophysica acta, 2005)
A 291-kDa lectin (LsL) was purified from the hemolymph of the white shrimp Litopenaeus setiferus by affinity chromatography on glutaraldehyde-fixed stroma from rabbit erythrocytes. LsL is a heterotetramer of two 80-kDa and two 52-kDa subunits, with no covalently-liked carbohydrate, and mainly composed by aspartic and glutamic acids, glycine and alanine, with relatively lower methionine and cysteine contents. Edman degradation indicated that the NH2-terminal of the 80-kDa subunit is composed DASNAQKQHDVNFLL, whereas the NH2-terminal of the 52-kDa subunit is blocked. The peptide mass fingerprint of LsL was predicted from tryptic peptides from each subunit by MALDI-TOF, and revealed that each subunit showed 23 and 22%, respectively, homology with the hemocyanin precursor from Litopenaeus vannamei. Circular dichroism analysis revealed beta sheet and alpha helix contents of 52.7 and 6.1%, respectively. LsL agglutinate at higher titers guinea pig, murine, and rabbit erythrocytes its activity is divalent cation-dependent. N-acetylated sugars, such as GlcNAc, GalNAc, and NeuAc, were the most effective inhibitors of the LsL hemagglutinating activity. Sialylated O-glycosylated proteins, such as bovine submaxillary gland mucin, human IgA, and fetuin, showed stronger inhibitory activity than sialylated N-glycosylated proteins, such as human orosomucoid, IgG, transferrin, and lactoferrin. Desialylation of erythrocytes or inhibitory glycoproteins abolished their capacity to bind LsL, confirming the relevance of sialic acid in LsL–ligand interactions.